Identification of cancer-associated fibroblast signature genes for prognostic prediction in colorectal cancer - Jin, Wei; Lu, Yuchang; Lu, Jingen; Wang, Zhenyi; Yan, Yixin; Liang, Biao; Qian, Shiwei; Ni, Jiachun; Yang, Yiheng; Huang, Shuo; Han, Changpeng; Yang, Haojie (Frontiers in Genetics, 2025)
BackgroundCancer-associated fibroblasts are an essential part of the tumor immunoenvironment, playing key roles in malignancy progression and treatment response. This study was to characterize cancer-associated fibroblasts-related genes (CAFs) in colorectal cancer (CRC) and establish signature genes associated with CAF for prognosis prediction.MethodsWe downloaded single-cell RNA sequencing (scRNA-seq) data from the GEO database and bulk RNA-seq data from TCGA database to identify differentially expressed genes related to fibroblasts. In the TCGA set, DEGs were identified from tumor samples, and the WGCNA method was utilized to identify module genes. By comparing the WGCNA module genes with tumor fibroblast-related DEGs, we took the overlapped cohorts as crucial CAFs. Moreover, the prognostic CAFs were identified using univariate analysis. A CAFs risk model was established using the LASSO algorithm and then validated using external datasets. Ultimately, the expression of prognostic CAFs in CRC was confirmed using qRT-PCR.ResultsA large cohort of DEGs were identified as CAFs, with eight demonstrating prognostic significance. These CAFs were primarily related to seven pathways, including peroxisome function, B cell receptor signal, and cell adhesion molecule. The CAFs risk model exhibited high accuracy for predicting prognosis, as confirmed through validation using external independent cohorts. Additionally, the risk signature showed significant correlations with immune-related scores, tumor purity, estimate, and stromal scores. qRT-PCR validated that the expression level of RAB36 was significantly downregulated in the HCT116 and HT29 cell lines compared to the NCM460 cells. Conversely, CD177, PBX4 and CCDC78 were upregulated in the HCT116 and HT29 cell lines, and ACSL6 and KCNJ14 only in HCT116 cells (P < 0.05). The expression trends of CD177 and CCDC78 were consistent with our predicted results.ConclusionThe CAFs risk model accurately predicted prognosis, immune cell infiltration, and stromal estimates. The prognostic CAFs (CD177 and CCDC78) may be potential therapeutic targets for CRC.